2021
DOI: 10.3389/fpsyt.2021.685711
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Brain 18F-FDG PET Imaging in Probable Seronegative Encephalitis With Catatonia: A Case Report

Abstract: Autoimmune encephalitis (AIE) is a rare, severe, and rapidly progressive encephalopathy, and its diagnosis is challenging, especially in adolescent populations when the presentation is mainly psychiatric. Currently, cerebral 18-fluorodeoxyglucose positron emission tomography (18F-FDG-PET) imaging is not included in the diagnosis algorithm. We describe a 16-year-old patient with probable seronegative encephalitis with catatonia for which several cerebral PET scans were relevant and helpful for diagnosis, treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, there is reluctance in the usage of nuclear imaging in pediatric patients due to the perception of the radiation burden associated with this technique, so cases should be carefully selected (29). It has been suggested that 8F-FDG PET might have a diagnostic role in autoantibody-negative encephalitis and that it might play a role in monitoring of the immunosuppressive response (27,30), even in pediatric population (31), but further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is reluctance in the usage of nuclear imaging in pediatric patients due to the perception of the radiation burden associated with this technique, so cases should be carefully selected (29). It has been suggested that 8F-FDG PET might have a diagnostic role in autoantibody-negative encephalitis and that it might play a role in monitoring of the immunosuppressive response (27,30), even in pediatric population (31), but further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that brain 18F-FDG PET should be included in future diagnostic autoimmune encephalitis recommendations (brain 18F-FDG PET has a high detection sensitivity and should be included in future diagnostic autoimmune encephalitis recommendations) [63]. Finally, a specific NavigaƟng neuroinflammatory disorders in children and adolescents: Diagnosis interest of PET scan for patients with seronegative autoimmune encephalitis or probable autoimmune encephalitis (normal MRI and no specific CSF antibodies) has been raised with challenging paediatric case successfully presumptively treated with immunosuppressive treatments after a positive PET scan [64][65][66][67].…”
Section: Neuroimagingmentioning
confidence: 99%